Material management in themed restaurants : Inspiring the experience economy / Farah Adibah Che Ishak, Philip Crang and Muhammad Shahrim Ab Karim - Che Ishak, Farah Adibah; Crang, Philip; Ab Karim, Muhammad Shahrim (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
In tune with wider ideas of an experience economy, the hospitality industry has increasingly focused less on giving a service to its customers and more on offering them memorable, sensory experiences. This paper looks at one facet of this provision of experiences: the material engineering and management of the ‘affective atmosphere’ or ‘ambiance’ of a venue. It unfolds the exploration of theme restaurants in practicing the material management as an inspiration to stage an experience. This paper illustrates its arguments through one case study: the Indonesian theming of the Pondok Malindo restaurant, Selangor. Practically, the findings suggest that creating the desired ambiance needs proper planning and careful attention to a wide range of material elements. More broadly, the paper suggests that accounts of the experience economy should consider the powers and agencies of materials and objects.